AUTOMATED CREATION OF EDUCATIONAL QUESTIONS: ANALYSIS OF ARTIFICIAL INTELLIGENCE TECHNOLOGIES AND THEIR ROLE IN EDUCATION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
This study explores the integration of artificial intelligence (AI) in education, focusing on its potential benefits and challenges. Through an in-depth analysis of contemporary AI platforms and software technologies, it examines their suitability for educational environments. The study highlights AI's capacity to enhance personalized learning experiences, facilitate educational gaming and simulations, and support teachers in various tasks. However, ethical considerations regarding data privacy and algorithmic bias, as well as technical challenges related to software reliability, require careful attention. By providing insights into the transformative potential of AI in education, this research aims to inform stakeholders about the opportunities and risks associated with its implementation.